Hydrothermal synthesis of rGO-PbBi2Se4 composite and investigation of its structural, chemical and field emission properties - Aher, Rahul; Bhorde, Ajinkya; Sharma, Priyanka; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Rondiya, Sachin; Chaudhary, Minakshi; Gopinath, Chinnakonda; Suryawanshi, Sachin; More, Mahendra; Jadkar, Sandesh (Journal of Materials Science-Materials in Electronics, 2018)
In the present study we report the one step facile synthesis of pristine lead bismuth selenide (PbBi2Se4) and reduced graphene oxide (rGO) and its composites with PbBi2Se4. Formation of pristine PbBi2Se4 and rGO-PbBi2Se4 composite were confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The surface morphology and topography investigated by using scanning electron microscopy and transmission electron microscopy revealed the formation of nano-flowers pristine PbBi2Se4. After coupling pristine PbBi2Se4 with rGO the surface morphology shows the formation of sharp vertically protruded nano-sheets/nano-flaks originated from the nano-flowers. Finally, the field emission properties of pristine PbBi2Se4 and rGO-PbBi2Se4 composite have been investigated. It has been observed that the rGO-PbBi2Se4 composite emitter exhibited excellent field emission properties with low turn-on field (similar to 2.8 V/A mu m for 10 A mu A/cm(2)), high emission current density (similar to 1288 A mu A/cm(2) at 3.9 V/A mu m) and superior current stability (similar to 4.5 h for similar to 1 A mu A) compare to pristine PbBi2Se4 emitter. Thus, the facile one step synthesis approach and robust nature of rGO-PbBi2Se4 composite emitter can provide prospects for the future development of large-area emitter applications such as flat-panel-display and vacuum micro/nanoelectronics devices.

Role of palladium crystallite size on CO oxidation over CeZrO 4-δ supported Pd catalysts - Burange, Anand S.; Reddy, Kasala Prabhakr; Gopinath, Chinnakonda; Shukla, Rakesh; Tyagi, Avesh K. (Journal of Molecular Catalysis, 2018)
Photodeposited palladium on nanocrystalline CeZrO 4-δ support was evaluated for CO oxidation, as a function of particle size and pre-treatment. All the catalysts were well characterized by XRD, SEM, EDX, TEM, CO chemi-sorption and Raman spectroscopy. It was observed that change in photodeposition time alters the average crystallite size of Pd, and the same was confirmed by CO chemisorption. 7 nm average crystallite size of Pd exhibited excellent catalytic activity for CO oxidation. In order to understand the effect of support and metal-support interaction, 1 wt% Pd was deposited deliberately onto reduced and oxidized CeZrO 4-δ support. The reduced support with anionic vacancies and more Ce 3+ species exhibited an improvement in CO oxidation at onset temperature. Detailed analysis shows that Pd-deposition occurs preferentially at oxygen-vacancy sites and subsequent metal-support interaction influences the catalysis.

Photocatalytic hydrogen production from H2S using nanostructured CNT blended CdZnS/Fe2O3 thin film on glass substrate - Raja, M. Anthony; Vijayarengan, Preethi; Pal, Yash; Nalajala, Naresh; Gopinath, Chinnakonda (Journal of Physics Conference Series, 2020)
<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A co-precipitation method was employed to prepare the CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst. Using the powder photocatalyst, the thin film of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst over a glass substrate was prepared using the drop-casting method. The obtained thin film was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive X-ray analysis (EDAX), photoluminescence (PL), and hydrogen production activity studies in order to obtain information on their structural, morphology, chemical composition, optical and hydrogen production efficiency. The hydrogen production activity of catalyst or effective conversion of H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S into hydrogen (H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) and sulfur (S) using thin-film photocatalyst was evaluated using a simulated sulfide solution. The results showed that 1 mg of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst coated as thin film over glass substrate (4.69 cm<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) showed the highest hydrogen production value of 3180 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">; compared to that of 1 mg CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> powder of 2510 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. From the above results, it is concluded that the thin film form of photocatlyst produced more hydrogen than the powder form. This is attributed to the effective charge separation and increased specific surface area in thin film photocatalyst.

Shape-controlled metal oxides for selective catalytic oxidation - Burange, Anand S.; Gopinath, Chinnakonda (Advanced Heterogeneous Catalysts Volume 1: Applications at the Nano-Scale, 2020)
Some of industrial processes involve selective oxidation reactions that include the use of corrosive and nonbenign oxidants and solvents. Many metal oxide-based catalysts have been reported for selective oxidation processes, and they exhibit a range of activities compared to homogeneous protocols and current practices. To bridge the gap between homogeneous and heterogeneous catalysis in terms of activity and selectivity and move toward green oxidation processes, this chapter discusses the shape-controlled synthesis of a selected range of metal oxides and their applications in selective catalytic oxidation reactions. This chapter also discusses some of the interesting micro- and nanostructured materials used in these reactions, as well as the roles of exposed predominant facets, defects, and other features and their effects on catalysis. Oxides of Mn, Co, Ce, Cu, Fe, La, and some combinations thereof are presented. Chemical reactions such as the selective oxidations of alcohol, ethyl benzene, styrene, xylene, and 5-hydroxymethylfurfural and the preferential oxidation of CO are also discussed.

Review on the recent advances in the design and structure–activity relationship of TiO2-based photocatalysts for solar hydrogen production - Mani, Sunesh S.; Rajendran, Sivaraj; Mathew, Thomas; Gopinath, Chinnakonda (Energy Advances, 2024)
The major issues that determine the efficiency of photocatalyst composite materials for solar hydrogen production, with or without a sacrificial agent, are efficient visible light harvesting properties, efficient separation of charge carriers and their utilization of redox sites, and stability. Thus, significant efforts have been devoted in the past few decades to modify the above characteristics by integrating constituent components of composites using different approaches. In the present review, we aim to summarize the recent advances, predominantly, in the area of TiO2-based photocatalyst composites for solar hydrogen production. Firstly, we present the recent progress in material integration aspects by discussing the integration of TiO2 with different categories of materials, including noble/3d metals, metal oxides/sulphides/selenides, other low bandgap semiconductors, C-based materials, and dye sensitizers. Furthermore, we discuss how material integration helps in tailoring the electronic and optical properties for activity tuning in solar H2 production. Subsequently, critical changes in the physico-chemical and electronic properties of composites with respect to their preparation methods, morphology, crystallographic facets, particle size, dopant, calcination temperature, and structure–activity relationship to solar hydrogen production are addressed in detail. Moreover, we discuss the importance of fabricating a photocatalyst in a thin film form and performing solar hydrogen production in different reactor set-ups for enhancing its photocatalytic performance, while addressing device scalability. Despite the significant advancements made in this field, solar-to-hydrogen conversion efficiency still needs to be improved to realise the practical application of solar hydrogen production. In this case, the direct conversion of water to hydrogen via overall water splitting and renewable H2 production from wastewater or biomass components by employing suitable photocatalysts are some possible ways to improve the energy efficiency, and continuous research in the above directions is highly desirable.